A Text-Driven, Task-Based Approach to the Design of Materials for Teaching Intercultural Communicative Competence - Harper, John (Journal of English Language Teaching and Linguistics, 2019)
Although a large body of research points to the need of providing English as a Foreign Language (EFL) learners with intercultural communicative competence (ICC), questions remain as to exactly how ICC should be incorporated into the EFL curriculum. These questions arise in part due to issues of already-packed curricula which seem not to leave time for the teaching of ICC and in part due to issues of teacher preparedness. Additionally, questions arise concerning which culture should be taught. Taking into account materials used in the English Language Center (ELC) of Shantou University (Guangdong Province, China), this paper argues that a text-driven, task-based method of materials design allows for the inclusion of ICC across the EFL curriculum. It also argues that such a method lends itself to the teaching of ICC through a consideration of a variety of cultures.